2017
DOI: 10.3892/ol.2017.6512
|View full text |Cite
|
Sign up to set email alerts
|

5FU resistance caused by reduced fluoro-deoxyuridine monophosphate and its reversal using deoxyuridine

Abstract: Abstract. The mechanism of 5-fluorouracil (5FU) resistance was investigated, focusing on the level of thymidylate synthase (TS) ternary complex formed with fluoro-deoxyuridine monophosphate (FdUMP). MKN45 and 5FU-resistant MKN45/F2R cells were treated with 5FU and fluoro-deoxyuridine (FdU) in combination with deoxyuridine (dU) and thymidine (dT). Subsequently, the levels of ternary complex were determined by western blotting and the cell viability was calculated using an MTT assay. MKN45/F2R cells exhibited 5F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…We previously elucidated the mechanism of acquired 5FU resistance by focusing on the changes in the expression levels of enzymes for 5FU metabolism in gastric cancer cell lines ( 12 , 13 ). In this study, we investigated the mechanisms of acquired 5FU resistance in colon cancer cell lines by investigating the changes in the related enzymes and the amount of synthesized FdUMP.…”
Section: Introductionmentioning
confidence: 99%
“…We previously elucidated the mechanism of acquired 5FU resistance by focusing on the changes in the expression levels of enzymes for 5FU metabolism in gastric cancer cell lines ( 12 , 13 ). In this study, we investigated the mechanisms of acquired 5FU resistance in colon cancer cell lines by investigating the changes in the related enzymes and the amount of synthesized FdUMP.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the monotherapy by raltitrexed is sometimes suggested for the patients with advanced colorectal cancer refractory to the 5-FU [30], our data show that the resistance to 5-FU was associated with the cross-resistance to this drug as well. Decreased OPRT and increased TS levels connected to the 5-FU resistance on a model of gastric cancer cell line were demonstrated [31]. We showed that the decreased OPRT expression potentially leading to inefficient 5-FU metabolic conversion might be partially compensated by the co-culture of the tumor cells with the MSC expressing CD::UPRT.…”
Section: Discussionmentioning
confidence: 74%
“…Importantly, it should be noted that total TS, the free form, the FdUMP-covalent form, and total TS was overexpressed in HCT116R F10 cells rather than in HCT116 cells ( Figure 6 a top panel and Figure 6 d). The upper band of TS, indicated FdUMP-covalent form, which represents TS in ternary complexes and is correlated with the intracellular concentration of FdUMP [ 12 , 13 , 14 ]. In addition, DPD protein levels were slightly decreased in HCT116R F10 cells than in parental HCT116 cells ( Figure 6 a second panel and Figure 6 e).…”
Section: Resultsmentioning
confidence: 99%